Efficacy of sodium metabisulphite for control of Aspergillus flavus and aflatoxin B1 contamination in vitro and in chilli powder and whole red chillies. (May 2022) - Al-Jaza, Diyaa; Medina, Angel; Magan, Naresh
Abstract: Chillies are an important spice in many regions of the world. During the production and processing phases, they are prone to infection by mycotoxigenic fungi, especially Aspergillus Section Flavi species and contamination with aflatoxins. There is significant interest in controlling aflatoxin B1 (AFB1 ) contamination in such spices to ensure they remain below the legislative limits for human consumption. This study initially examined the potential efficacy of sodium metabisulphite (NaMBS, up to 5000 mg/L) for the control of growth and AFB1 production by Aspergillus flavus strains in vitro on a chilli-based medium modified to 0.93–0.995 water activity, aw ). Subsequent studies examined efficacy of NaMBS in stored naturally contaminated chilli powder and whole red chillies, or when inoculated with A. flavus at 0.70, 0.80, 0.90, 0.95 aw and 30 °C for 20 days. NaMBS was effective in vitro in controlling growth of the three strains of A. flavus at the different aw levels examined. No growth occurred with >500–1250 NaMBS mg/L. AFB1 was only produced at 0.98 aw with complete inhibition at ≥1250 mg/L of the preservative at 30 °C. The in vitro ED50, ED90 for NaMBS varied with aw conditions. In situ studies with chilli powder and whole red dry chillies (naturally contaminated or + conidial inoculum of A. flavus ) showed that at 0.70 and 0.80 aw, NaMBS treatments of 1000 and 2000 mg/L resulted in AFB1 contamination levels below the legislative limits for spices. However, under wetter conditions at 0.90 and 0.95 aw, AFB1 contamination of stored chilli powder, −/+ A. flavus inoculum, were above the legislative limits, even with 2000 mg/L NaMBS and 20 days storage at 30 °C. Stored whole chillies inoculated with A. flavus resulted in a reduction of populations, especially at 2000 mg/L NaMBS. Control of AFB1 was achieved only with 2000 mg/L NaMBS treatment after 10 and 20 days storage. Studies with commercial laminated sheets containing immobilised NaMBS with slow release of SO2 properties significantly reduced fungal populations and effectively controlled AFB1 contamination of the stored and packaged whole red chillies. Highlights: In vitro control of growth/aflatoxin B1 was effective using sodium metabisulphite. Effective doses for control in vitro and in situ was affected by water availability. In situ control of toxin in chilli powder required 1000–2000 mg/L at <0.80 aw +30 °C. Control of toxin at 0.90 and 0.95 aw stored whole red chillies required 2000 mg/L. Sheets with slow release SO2 reduced A. flavus CFUs and toxin in whole chillies.